Effect of tissue-type plasminogen activator on platelet aggregation - SHIRAKAWA, Shigeru; MURASHIMA, Seiko; NISHIKAWA, Katsumasa; DEGUCHI, Akira; TUDA, Masayuki; SUZUKI, Hikoji; DEGUCHI, Katsumi; MORI, Yoshitaka; WADA, Hideo; IWASAKI, Hideo (Blood & Vessel, 1988)
The effects of tissue-type plasminogen activator (t-PA) on platelet aggregation in platelet rich plasma (PRP) or washed platelets from healthy subjects were studied. Platelet aggregates induced by ADP in PRP dissociated immediately after the addition of t-PA (15×104IU/ml). This disaggregation was dependent upon the concentration of t-PA (2-3O×104IU/ml), time for the addition of it after ADP (30-180sec.), and the aggregation ability of platelet itself. Platelet aggregates in PRP, added α2-plasmin inhibitor (final concentration: f. c.; 1IU/ml) to, dissociated in response to t-PA but not to plasmin (f. c.; 1.5CU/ml), although t-PA and plasmin induced the dissociation of them in PRP that α2-PI was not added to. When t-PA or plasmin was added to washed platelet aggregates induced by ADP in the presence of fibrinogen with or without plasminogen, t-PA induced the dissociation of them and plasmin enhanced the extent of them. These findings suggest that t-PA induced platelet disaggregation relates to the interaction among platelet, fibrinogen and t-PA, in addition to action of plasmin generated following plasminogen activation by t-PA on the platelet surface.